(untitled) (American International Journal of Economics and Finance Research, 2021)
Creating new financial product and its development phases contain on the problematic but a witty process. This research article’s Objective is to check out the development of novel product and also checking its impacts on the organization’s performance. It has a budding pouring element on the performance of any organization, when it developed. Methodology: Primary and secondary both data, along with t-test applied in this research article. Sample: 250 regular clients of the commercial banks. Research journals, bank’s prospects reports were very helping as secondary data in this regard. Partial least squares (PLS) also applied for hypothesis testimonial. Values of the Cronbach’s coefficient alpha more than 0.70. New innovation product development, Relational Performance, Customer’s Satisfaction uses as (DV) collectively, and 1- firm image, on second brand strength, on third market sensing capability, on fourth product innovativeness, on fifth new product quality used as (IVs). Results: shows that with the development of ‘new innovative products’ firm also accelerates its business volume. Firms get the new clients and improve existing relationship. Brand of firm got the new identity and even reach to unknown persons. Market share level upsurge. Innovativeness of product creates flourishing image and market share. Findings: of this research article was the multiple four factors: Brand strength, new product quality firm image, Product innovativeness. In findings ‘r’ (correlation) and ‘r2’ (regression) shows the strong and positive relationship flanked-by DVs and IVs. There were some restrictions in this research article that will be resolved voguish the impending research & exploration direction.